2020
DOI: 10.1002/mc.23184
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate synergistically induces apoptosis with Gefitinib in non–small cell lung cancer cells via endoplasmic reticulum stress‐mediated degradation of Mcl‐1

Abstract: Isothiocyanates (ITCs) are natural compounds abundant in cruciferous vegetables.Numerous studies have shown that ITCs exhibit anticancer activity by affecting multiple pathways including apoptosis and oxidative stress, and are expected to be developed into novel anticancer drugs. In our previous studies, we demonstrated that ITCs effectively inhibit the proliferation of non-small cell lung cancer (NSCLC) cells, also induce apoptosis and autophagy. In the present study, we found that phenethyl isothiocyanate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
(115 reference statements)
0
20
0
Order By: Relevance
“…Western blottings were performed as previously described ( Zhang Q. et al, 2020 ). Cells were treated with RIPA lysis buffer (Beyotime Biotechnology, China) containing protease inhibitor (Sigma- Aldrich) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Western blottings were performed as previously described ( Zhang Q. et al, 2020 ). Cells were treated with RIPA lysis buffer (Beyotime Biotechnology, China) containing protease inhibitor (Sigma- Aldrich) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, anti‐apoptotic factors such as Bcl‐2 demonstrate a decrease in expression, while pro‐apoptotic factors such as Bax undergo upregulation. By releasing cytochrome C from mitochondria, caspase cascade begins that finally results in apoptotic cell death (Chong et al, 2020; Li, Tian, Liang, & Li, 2020; Zhang et al, 2020). In impairing proliferation and invasion of melanoma cells, CT targets apoptosis.…”
Section: Cryptotanshinone and Cancermentioning
confidence: 99%
“…For example, dhalcomoracin has been shown to inhibit cell proliferation and increases sensitivity to radiotherapy in NSCLC by inducing ER stress (Zhang et al 2020b). Phenethyl isothiocyanate in combination with Gefitinib induces apoptosis in NSCLC cells through ER stress-mediated Mcl-1 degradation (Zhang et al 2020a). The present study revealed that CASC2 promoted apoptosis and radiosensitivity of NSCLC cells principally by enhancing the PERK/eIF2α/CHOP ER stress signaling pathway.…”
Section: Discussionmentioning
confidence: 49%